Parents’ and guardians’ perceptions on availability and pricing of medicines and healthcare for children in eThekwini, South Africa – a qualitative study - Perumal-Pillay, Velisha Ann (BMC Health Serv Res, 2017)
BACKGROUND: Inadequate access to affordable essential medicines poses a challenge to achieving Universal Health Coverage. Access to essential medicines for children has been in the spotlight in recent research. However, information from the end users of medicines, i.e. patients is scarce. Obtaining information at a household level is integral to understanding how people access, obtain and use medicines. This study aimed to gather opinions and perceptions from parents/guardians on availability, affordability and quality of medicines and healthcare for children in SA. METHODS: Eight Focus group discussions were held with 41 individuals in eThekwini, South Africa (SA), from September–November 2016. Participants were parents/guardians of children up to 12 years from different ethnicities, ages, gender, and socio-economic backgrounds. Key informants identified by the principal researcher recruited participants using snowball sampling. Focus group discussions were recorded, transcribed verbatim, coded by the first author, verified by the second author, reconciled for consensus and imported into NVIVO for data analysis. RESULTS: Medicines and healthcare facilities are accessible in urban and peri-urban areas in eThekwini. Medicines may not always be available in public sector facilities due to medicine shortages, compelling parents to purchase medicines from private sector pharmacies. Common medicines were perceived as affordable for most socio-economic groups except the ‘Poor’ group. Quality of medicines was perceived as ‘good’ especially if obtained from the private sector but sometimes perceived as ‘poor’ and viewed with suspicion when received from public sector clinics. Quality of healthcare was perceived as ‘good’ but requires improvement for both sectors. CONCLUSIONS: This is the first study in SA to report on parent/guardian perceptions on availability, affordability and quality of medicines and healthcare for children. It has the potential to be up-scaled to a country-wide investigation to paint a national picture of parents’ opinions of healthcare for children. This will allow for patient input into pharmaceutical and healthcare policy governing access to and availability of essential medicines and services within the country. The study recommends that patient input be sought to assess impact of policies on the intended target group in the country to ensure that the policy objectives are achieved. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12913-017-2385-y) contains supplementary material, which is available to authorized users.